CORPORATE GOVERNANCE, PROFITABILITY, AND FIRM VALUE STUDY ON THE INDONESIAN SHARIA STOCK INDEX - Sutrisno, Sutrisno (Universitas Airlangga, 2020)
The purpose of this study is to examine the effect of corporate governance mechanisms and profitability on firm value. The corporate governance mechanism consists of a board of directors, a board of commissioners, managerial ownership, and institutional ownership. Firm value is measured by Tobin's Q, while profitability is measured by return on assets. The population in this study were companies listed on the Indonesian Sharia Stock Index with a total sample of 103 companies taken by purposive sampling method. The observation period is for five years from 2015 to 2019. To test the hypothesis, the author applies panel data regression analysis. In selecting the panel data model, after being tested, the best model is the fixed effect model. The results of the research based on the fixed effects model show that the board of commissioners has a significant but negative effect on firm value, while the board of directors and profitability and ownership of institutions have a significant and positive effect on firm value, but managerial ownership has no significant effect on firm value.